2015
DOI: 10.4187/respcare.04196
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia During Extreme Hyperleukocytosis: How Spurious?

Abstract: BACKGROUND: Spurious hypoxemia has been described in case reports during extreme hyperleukocytosis and has led to recommendations for immediate cooling and analysis of arterial blood gases (ABGs). We sought to determine, in samples processed as recommended, the magnitude of spurious hypoxemia in acute leukemia subjects with hyperleukocytosis. METHODS: A retrospective chart review was conducted of all subjects admitted between 2003 and July 2014 for acute leukemia, who presented with white blood cell (WBC) coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…A study systematically investigated the magnitude of spurious hypoxemia in 45 patients with acute leukaemia and hyperleukocytosis, and found a poor correlation between SaO 2 and SpO 2 in the presence of a white blood cell count above 100,000 mm 3 , grossly proportional to white blood cell count and time to analysis of blood gases [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
“…A study systematically investigated the magnitude of spurious hypoxemia in 45 patients with acute leukaemia and hyperleukocytosis, and found a poor correlation between SaO 2 and SpO 2 in the presence of a white blood cell count above 100,000 mm 3 , grossly proportional to white blood cell count and time to analysis of blood gases [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Work done in leukaemic patients with excessively raised white cell counts, shows "pseudohypoxaemia". [6][7][8][9][10][11][12][13] This is due to continued To accurately assess this effect, the samples were kept in glass syringes, since plastic syringes are permeable to gases. 14,15 Previous work showed reductions in PO 2 at 30 minutes ranging from -0.8 kPa to + 1.07 kPa when the sampled blood was stored in plastic syringes at ambient temperature, and an exaggerated response when stored on ice, with deviations between +0.8 kPa and + 1.8 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of RESPIRATORY CARE, Van de Louw et al 1 describe the magnitude of spurious hypoxemia as suggested by arterial blood gases (ABGs) obtained from subjects with acute leukemia and hyperleukocytosis. Spurious hypoxemia, commonly known as leukocyte larceny, is just one of several erroneous values or discrepancies with pulse oximetry and the bedside assessment (or bioassay) that may occur when obtaining or interpreting ABGs.…”
mentioning
confidence: 99%